Are Exercise Therapy Protocols For The Treatment of Hip-Related Pain Adequately Described? A Systematic Review of Intervention Descriptions - August Estberger; Joanne L Kemp; Kristian Thorborg; Anders Pålsson; Eva Ageberg (International Journal of Sports Physical Therapy, 2023)
# Background